Analysis of LiFePO4 Cathodic Active Material Synthesized in Open Environment Conditions through Ionic Medium. Issue 1774 (2015) - Kwee, Darren W.; Lim, Taehoon; Martinez-Morales, Alfredo
ABSTRACT: In this work, LiFePO4 (LFP) particles were synthesized through an ionic liquid medium. Through the fabrication of LFP particles, we observed the formation of quasi-1−dimensional (1D) structures. The characterization of phases found in the reaction, through time-dependent studies, have led us to propose a possible scheme for particle formation. Synthesized material was characterized by scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), and x-ray diffraction (XRD). We also report our analysis on particle morphology and crystallinity of LFP particles synthesized through an ionic liquid−mediated process.